Swiftly judging whom to bring on board: How person perception (accurate or not) influences selection of prospective team members - Derfler-Rozin, Rellie; Isaakyan, Sofya; Park, Hyunsun (Organizational behavior and human decision processes, 2022)
•Perceptions of a prospective team member’s competence shape predicted task related performance in the team.•Perceptions of prospective team member’s warmth shape predicted interpersonal contextual performance in the team.•Selection decisions are driven more by predicted task (vs interpersonal contextual) performance.•Importance of predicted interpersonal contextual performance elevates in a context of teams high on task interdependence.•Predicted task related performance is quite accurate and relates to actual task related performance in the team.•Predicted interpersonal contextual performance does not relate to actual performance in the team, making reliance on it for team member selection erroneous. We develop and test a holistic model of how team members’ swift judgments about a prospective team member impact their selection decisions and how accurate those judgments are in predicting the prospective member’s performance. Applying the social psychology literature on person perception to the organizational literature on team member selection, we argue that team members’ perceptions of the prospective member’s competence primarily shape their predictions about the prospective member’s task-related performance in the team, whereas perceptions of warmth primarily shape predictions about the prospective member’s interpersonal contextual performance in the team. We further propose that, although team members rely on both performance predictions when choosing a prospective member, predicted task-related performance receives more weight than predicted interpersonal contextual performance, and that the importance of predicted interpersonal contextual performance is elevated when team task interdependence is high. Importantly, we theorize that the predictions about task-related performance show good accuracy, whereas the predictions about interpersonal contextual performance do not, which makes the reliance on the latter erroneous. Across two studies utilizing prospective members’ actual task-related and interpersonal contextual performance (objective and peer-rated), as well as team members’ predictions about such performances, we found support for our predictions. Our research resolves several outstanding puzzles in the literature on person perception, integrates it into organizational research, and offers novel and actionable insights for selecting prospective team members.